2011
DOI: 10.1002/eco.132
|View full text |Cite
|
Sign up to set email alerts
|

Thermopeaking in Alpine streams: event characterization and time scales

Abstract: The present study provides a detailed quantification of the 'thermopeaking' phenomenon, which consists of sharp intermittent alterations of stream thermal regime associated with hydropeaking releases from hydroelectricity plants. The study refers to the Noce River (Northern Italy), a typical hydropower-regulated Alpine stream, where water stored in high-altitude reservoirs often has a different temperature compared with the receiving bodies. The analysis is based on a river water temperature dataset that has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
139
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(155 citation statements)
references
References 34 publications
13
139
1
2
Order By: Relevance
“…The risk of drift for aquatic organisms is strongly affected by the morphological condition of the river and the density of refuges (Young et al 2011). Water is turbinated through the powerhouses directly from reservoirs; thus, in the winter, a rapid increase in discharge occurs in combination with a sudden increase in water temperature, which influences the behavior of invertebrates (Carolli et al 2012;Zolezzi et al 2011). Bruder et al (2012 reported that brown trout have difficulty moving up in the Alpine Rhine in a high speed flow and that the fish try to reach shelters to conserve energy.…”
Section: Negative Effects Of Hydropeaking and Fish Behaviormentioning
confidence: 99%
“…The risk of drift for aquatic organisms is strongly affected by the morphological condition of the river and the density of refuges (Young et al 2011). Water is turbinated through the powerhouses directly from reservoirs; thus, in the winter, a rapid increase in discharge occurs in combination with a sudden increase in water temperature, which influences the behavior of invertebrates (Carolli et al 2012;Zolezzi et al 2011). Bruder et al (2012 reported that brown trout have difficulty moving up in the Alpine Rhine in a high speed flow and that the fish try to reach shelters to conserve energy.…”
Section: Negative Effects Of Hydropeaking and Fish Behaviormentioning
confidence: 99%
“…The hydrology of the Adige catchment (9700 km 2 at Trento), is mainly controlled by snow and glacier melting (e.g., [47][48][49]), although it is also significantly influenced by anthropogenic activities such as hydropower production [50] and agriculture [48]. The catchment is characterized by a sub-alpine climate with a long-term mean annual precipitation of 1022 mm.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Three important tributaries join the Adige River within the study area ( Figure 1A). The Noce River has a mean water discharge of 46 m 3 /s and a timing strongly modified by four hydropower plants located within its catchment [50]. From entrance in the Adige valley, it flows for 11 km before joining the Adige River.…”
Section: Site Descriptionmentioning
confidence: 99%
“…La distancia necesaria para la recuperación del ciclo térmico diario depende de la velocidad del río, caudal, anchura y procesos de intercambio de calor con la atmósfera (Prats et al, 2012). En algunos casos, además, las variaciones bruscas de caudal pueden conllevar cambios térmicos bruscos que pueden afectar a las poblaciones de macroinvertebrados (Zolezzi et al, 2010).…”
Section: Modificación Del Régimen Térmico Fluvialunclassified